2022
DOI: 10.3389/fonc.2022.875131
|View full text |Cite
|
Sign up to set email alerts
|

Immune Characteristics and Prognosis Analysis of the Proteasome 20S Subunit Beta 9 in Lower-Grade Gliomas

Abstract: Glioma is a common intracranial malignancy in adults and has a high mortality due to its poor prognosis and high recurrence rate. Dysregulation of protein degradation is one of the main promoting factors in glioma development. As an indispensable unit of the proteasome, Proteasome 20S Subunit Beta 9 (PSMB9) is one of the major enzymes in ubiquitin-dependent protein degradation in cells. In addition, proteasomes also participate in a series of cellular processing, like immune regulation, nerve signal transducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Thus, activation of PD-L1 gene expression coincided with the activation of immunoproteasome subunit expression following treatment with the inhibitor. Here it should be mentioned that upregulated PSMB8/9 expression correlated with increased efficacy of immune checkpoint inhibitors in melanoma ( Kalaora et al, 2020 ) and lower-grade glioma ( Liu et al, 2022 ). Interestingly, it has been shown that mutated forms of BRAF, NRAS, and KRAS can upregulate non-constitutive proteasome expression and reduce endoplasmic reticulum stress in multiple myeloma ( Shirazi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, activation of PD-L1 gene expression coincided with the activation of immunoproteasome subunit expression following treatment with the inhibitor. Here it should be mentioned that upregulated PSMB8/9 expression correlated with increased efficacy of immune checkpoint inhibitors in melanoma ( Kalaora et al, 2020 ) and lower-grade glioma ( Liu et al, 2022 ). Interestingly, it has been shown that mutated forms of BRAF, NRAS, and KRAS can upregulate non-constitutive proteasome expression and reduce endoplasmic reticulum stress in multiple myeloma ( Shirazi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In glioma cells, tumor suppressor genes are ubiquitin-labeled and degraded by the 26S proteasome 29 . The 20S proteasome, as its catalytic core, plays an important role in the degradation process of glioma tumor suppressor genes 30 . The lack of the 20S proteasome subunit makes glioma cells easy for the immune system to clear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, higher expression of PSMB9 tend to have better prognosis in breast invasive carcinoma (BRCA) 19 , ovarian serous cystadenocarcinoma (OV) 20 , and non-small cell lung cancer (NSCLC) 21 . However, higher expression of PSMB9 showed worse prognosis in lower-grade glioma (LGG) 22 . The study of PSMB9 in GC was still limited.…”
Section: Discussionmentioning
confidence: 99%